The dead can talk : Investigating trace element and organic pollutant exposure in mammalian roadkill under contrasting habitats - Molbert, Noëlie; Alliot, Fabrice; Goutte, Aurélie; Hansson, Maria C. ; 0000-0003-2711-4940 (Environmental Pollution, 2025)
Urban environments are exposed to a substantial range of anthropic pressures, including chemical exposure. While trace metals and legacy pollutants have been well documented, the extent of wildlife exposure to emerging contaminants has received little attention, in terrestrial mammals. Concentrations of trace elements (Ag, Al, As, Cd, Co, Cr, Cu, Fe, Mn, Pb and Zn) and 48 organic pollutants (Polychlorinated Biphenyls: PCBs, Organochlorine Pesticides: OCPs, Polycyclic Aromatic Hydrocarbons: PAHs, phthalates and pyrethroid pesticides) were measured in tissues of European hedgehogs (Erinaceus europaeus) in southern Sweden. Road kills and carcasses collected in 2021 and 2022 b y citizen science participants were used to characterize the level, tissue distribution and composition of mixtures in liver, spines and teeth samples. Phthalate diesters and PCBs were the most prevalent compounds in liver samples, with mean concentrations (±SD) of 1090 ± 681 and 284 ± 231 ng g−1 of dry weight, respectively. Bioaccumulation patterns were observed for some organochlorine compounds but were hampered by the small sample size. Trace element concentrations and tissue distribution were strikingly equivalent between tissue type and age-classes (juveniles and adults) of hedgehogs, except for a handful of elements (e.g., Pb, Al, As), but contamination profiles differed between habitat types. While no adverse health effects are expected to occur from the body burdens measured for most of the target analytes, concerns might be expressed for the exposure to PCBs, phthalates and some non-essential trace metals (e.g., lead >15 μg g−1 dw), which were found at levels above or approximating toxic thresholds in mammal tissues. The present study demonstrates the suitability of road kills as an alternative approach for environmental monitoring and the relevance of nondestructive biomonitoring to evaluate endogenous exposure in hedgehogs and possibly other terrestrial mammals and humans.
Keywords: Essential and non-essential elements; Hedgehogs; Mammals; PCB; Phthalates; Terrestrial ecosystems